The official (ISC) guide to the CCSP CBK - Gordon, Adam (John Wiley & Sons, Inc., 2016)
Globally recognized and backed by the Cloud Security Alliance (CSA) and the (ISC)2 the CCSP credential is the ideal way to match marketability and credibility to your cloud security skill set